Answer:
g(-4) = 1 g(5) = -3
Explanation:
Step 1: Recognize this is in function notation
In funcion notation what is in the brackets are the x coordinates of the point
Step 2: Solve
We see the first one is g(-4) so we head to the left side of the x-axis and look for a point on the line that has the x value of -4. We see that at x = -4 y is equal to 1 so g(-4) is equal to 1
Next we take a look at g(5) so we look at the right side of the x-axis and see that the line crosses x=5 at y=-3 so the value of g(5) is -3